How to read Foucault's Discipline and punish - Schwan, Anne; Shapiro, Stephen, 1964- (How to read theory., 2011)
"Michel Foucault's Discipline and Punish is one of the best-selling works of critical theory and a key text on many undergraduate courses. However, it is a long, difficult text which makes Anne Schwan and Stephen Shapiro's excellent step-by-step reading guide a welcome addition to the How to Read Theory series. Undergraduates across a wide range of disciplines are expected to have a solid understanding of Foucault's key terms, which have become commonplace in critical thinking today. While there are many texts that survey Foucault's thought, these are often more general overviews or biographical précis that give little in the way of robust explanation and discussion. In contrast, Schwan and Shapiro take a plain-speaking, yet detailed, approach, specifically designed to give students a thorough understanding of one of the most influential texts in contemporary cultural theory."--Back cover